Elaboration of an algorithm for wound evaluation and treatment. - Batista da Cunha, João; Alves Dutra, Rosimar Aparecida; Magela Salomé, Geraldo (Revista Estima, 2018)
Objectives: To develop an algorithm for evaluation and treatment of wounds and to test their internal reliability. Method: Crosssectional and descriptive study. For the construction of the algorithm, a review of the literature was realized with databases of health sciences and consultation of books and theses of this area published in the last 10 years, using as descriptors: acute and chronic wounds; wound evaluation; evaluation tools; dressings; nursing evaluation; wound healing and nursing care; and algorithms. Two hundred nurses with at least 12 months of experience in wound care were contacted and 38 of them completed the evaluation questionnaire. The internal consistency of the algorithm was measured by Cronbach's alpha coefficient. Results: All items evaluated had a "excellent" classification, being: graphic presentation (52.65%), readability (60.5%), sequence of the algorithm (52.6%), description of wound types (56.8%), description of tissue types (52.6%), presentation of types of exudate (57.9%), presentation of signs of infection (57.9%) and products to be used in dressing (50%). The algorithm presented excellent internal consistency (α = 0.911). According to 97.4% of the evaluations, the instrument is able to support health professionals in wounds evaluation. Conclusion: The algorithm showed internal reliability for evaluation and treatment of wounds.